Tingkat Kecemasan Ibu Yang Memiliki Balita Dalam Menghadapi Era New Normal - Rischa Pramudia Trisnani; Silvia Yula Wardani (JURKAM: Jurnal Konseling Andi Matappa, 2021)
This study aims to analyze the level of anxiety of mothers who have toddlers in facing the new normal era. This research is a descriptive qualitative research or survey. The sampling technique is random sampling. The sample in this study were 97 mothers who have toddlers. Data collection techniques in this study using a questionnaire with descriptive statistical analysis techniques. Based on the results of the data analysis technique, it shows that the condition of the anxiety level of mothers who have toddlers in facing the new normal era shows a high category. Mothers who have toddlers feel anxious, feel unusual tension, are afraid of large crowds and have sleep disorders because they have moody feelings that make mothers antisocial individuals.